2016
DOI: 10.1016/j.energy.2016.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Flow phenomena leading to surge in a centrifugal compressor

Abstract: Surge is a global flow instability occurring in centrifugal compressors at low mass-flow rate operation. Due to its violent nature, it is the limiting factor for operability. To enhance the operating range, understanding of the flow instability inception when approaching surge is essential. Therefore, the flow evolution along a speed line is analysed by performing unsteady, three-dimensional flow simulations using a centrifugal compressor geometry with ported shroud. A stable operating condition, at high mass-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 31 publications
(38 reference statements)
2
51
0
Order By: Relevance
“…Semlitsch et al [15, 16] could confirm by studying the same ported shroud compressor numerically that this reversed flow originates from the tip leakage and back flow jets generated via the ported shroud. Semlitsch and Mihăescu [17] suggested that the increased tip leakage swirling the inflow toward off design operating conditions degenerates the incidence flow angles such that the rotor blades might be incapable to maintain a constant back pressure and cause surging.…”
Section: Introductionmentioning
confidence: 99%
“…Semlitsch et al [15, 16] could confirm by studying the same ported shroud compressor numerically that this reversed flow originates from the tip leakage and back flow jets generated via the ported shroud. Semlitsch and Mihăescu [17] suggested that the increased tip leakage swirling the inflow toward off design operating conditions degenerates the incidence flow angles such that the rotor blades might be incapable to maintain a constant back pressure and cause surging.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, code validation is assessed alternatively by means of a grid dependency study, which is presented further below. Nevertheless, the solver has been used previously for calculating flow scenarios associated with centrifugal compressors at low mass flow rates and validations against experimental data were carried out, see [19][20][21].…”
Section: Numerical Methodologymentioning
confidence: 99%
“…Recent numerical work presented by the researchers of KTH [15,16,17] investigated the performance and acoustic characteristics of the ported shroud compressor operating near surge. Although authors [16] attempted to predict the value of surge frequency, relatively lower surge frequencies are seen in literature as the upstream and downstream duct volumes were not considered by the authors in the numerical model.…”
Section: Introductionmentioning
confidence: 99%